Pandangan dan Sikap Warga Jemaat terhadap Pengidap Skizofrenia (Studi di GMIT Jemaat Pniel Oebobo Klasis Kota Kupang) - Novi O. Eli Manafe; Ezra Tari; Nelman A. Weny (Sekolah Tinggi Teologi Berita Hidup, 2022)
The inadequate understanding of society about mental disorders results in people behaving less pleasantly for those who experience it. The purpose of this study was to determine the views of the congregation towards members of the congregation with schizophrenia mental disorders. The author wants to find the support provided by the congregation for members of the congregation who experience schizophrenia at GMIT Pniel Oebobo, Klasis Kota Kupang. The research method used is qualitative. This research was conducted to obtain data for specific purposes and uses. The results of the study found that the attitudes and judgments of the congregation towards people with schizophrenia were handled accordingly. The attitude of the respondent has a feeling of discomfort when he is close to someone with schizophrenia. The whole group was shrouded in fear. Behaviour different from normal humans is a striking feature of a person with schizophrenia. The attitudes of the majority of people whom the authors interviewed revealed that they chose to avoid it when it coincided with the person with schizophrenia.